2015
DOI: 10.1097/iae.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Sarcoid-Like Reactions and the Eye

Abstract: Sarcoid-like reactions can occur in the eye, and ocular malignancies may incite sarcoid-like reaction. Ocular sarcoid-like reactions have paraneoplastic features in that they can occur at a site distant from malignancy and may precede, occur simultaneously with, or follow malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
(38 reference statements)
2
9
0
Order By: Relevance
“…Our study also demonstrates that sarcoid‐reactions in malignancies might include uveitis (Balasubramaniam et al. ).…”
Section: Discussionsupporting
confidence: 74%
“…Our study also demonstrates that sarcoid‐reactions in malignancies might include uveitis (Balasubramaniam et al. ).…”
Section: Discussionsupporting
confidence: 74%
“…They showed that a SRSF2 P95 hotspot mutation, which usually occurs in 40–50% of CMML cases, was detected in skin and bone marrow biopsies in all of their cases . In our patient, the episcleritis and epithelioid cell‐like granuloma of the cervical lymph node resembled a sarcoid‐like reaction pattern, a process that resembles sarcoidosis but is secondary to an underlying disease such as CMML or other malignancies, also explaining the laboratory abnormalities such as serum neopterin, soluble interleukin‐2 receptor, beta 2 microglobulin and free light chains . Screening for underlying disease is therefore crucial in patients with PNGD and should include antinuclear antibodies, antineutrophilic cytoplasmic antibodies, rheumatoid factor, cyclic citrullinated peptide, a complete blood count with differential and electrophoresis with exclusion of a paraproteinemia.…”
supporting
confidence: 55%
“…The triggering mechanisms that induce sarcoid-like reactions may be categorized as following: 1) local reaction to infectious agents (leprosy, atypical mycobacterial infections, deep fungal reactions, etc.) [ 8 ][ 9 ][ 10 ]; 2) noninfectious but immunogenic antigens (inorganic compounds) [ 11 ][ 12 ]; 3) tumors (paraneoplastic sarcoid type of reaction) [ 13 ][ 14 ]. Our concepts of sarcoid - type reaction are based on the assumption that it may be provoked, in predisposed patients, by cross-reaction to immunogens or tumour antigens, so its pathogenesis is closely related to the generation of cross - mediated immunity presenting as molecular (antigen) mimicry.…”
Section: Discussionmentioning
confidence: 99%